Gender Equality in Food Security in Pandansari Lor Village, Jabung District, Malang Regency, East Java Province - Rangga Mahkota Ardi (Jurnal Perempuan dan Anak, 2022)
There are certainly many issues about gender that have been spread, with various kinds of facts being presented and exposed so that various types of scientific perspectives have emerged discussing gender. As if in rhythm but not in line with the Unitary State of the Republic of Indonesia which adheres to a democratized government system, of course, the results will not be the same in terms of gender discussions which are influenced by many faktors, even though countries in Asia, Africa and America both adhere to the notion of the same system of government that is democratic.The establishment of gender equality can certainly be determined by several faktors, if it occurs in the plurality of society in Indonesia with the high level of culture and the breadth of the geographical sector, a new perspective is required, namely the perspective of geographical conditions.The results of this study indicate that gender equality can be built fairly due to certain geographical faktors, but does not rule out biological, religious and cultural constructions. In fact, other results related to forms of gender discrimination such as marginalization, subordination, stereotypes, violence, double burden, were not found.